Analyzing and managing portfolio risk and performance using value-at-risk - Martins, Beatriz de Jesus Mendes (2024)
Globalization has enhanced the need to guarantee that financial institutions apply efficient risk management. Therefore, regulations strengthened the monitorization of risk management, by enforcing the minimum capital requirements and implementing Value-at-Risk (VaR) approach as a standard risk measurement metric. The main goal in this work is to use the VaR to analyze the performance and manage the risk of a portfolio composed of stocks and bonds from 4 different markets. First, we need to test the VaR models, by using the Backtesting approach to identify the model that provides the best fit, considering the portfolio composition and characteristics. Then, we use the more accurate model to measure and compare two approaches: the daily VaR of the portfolio without a risk management strategy and the daily VaR managed through a hedging strategy, for a period of one-year. Finally, we compare the performance of both strategies using a performance measure, the Return on Risk-Adjusted Capital (RORAC). The results indicate that the portfolio with a risk management strategy to limit the daily maximum VaR outperforms the portfolio without risk management.